Judging the Intensity of Emotional Expression in Faces: the Effects of Colored Tints on Individuals With Autism Spectrum Disorder. Issue 4 (8th June 2015) - Whitaker, Lydia; Jones, Catherine R.G.; Wilkins, Arnold J.; Roberson, Debi
Abstract : Individuals with autism spectrum disorder (ASD) often show atypical processing of facial expressions, which may result from visual stress. In the current study, children with ASD and matched controls judged which member of a pair of faces displayed the more intense emotion. Both faces showed anger, disgust, fear, happiness, sadness or surprise but to different degrees. Faces were presented on a monitor that was tinted either gray or with a color previously selected by the participant individually as improving the clarity of text. Judgments of emotional intensity improved significantly with the addition of the preferred colored tint in the ASD group but not in controls, a result consistent with a link between visual stress and impairments in processing facial expressions in individuals with ASD. Autism Res 2016, 9: 450–459 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.